Effect of Phytobiotic Mixture and Organic Acid Supplementation on Growth Performance, Haematobiochemical Profile and Carcass Traits of Broiler Chickens - Yadav, Alka; Gautam, Sachin; Singh, Vijay K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This study was undertaken to assess the effect of phytobiotic mixture and organic acid on the performance of broiler chickens. Day-old broiler chicks (n=250) were randomly divided into five groups with five replicates of 50 chicks and fed a basal diet with no supplement in the negative control (NC), supplemented with antibiotic (PC), alcoholic extract of 1.0% phytobiotic mixture (HE), 0.1% butyric acid (OA) and 1.0% phytobiotic mixture (alcoholic extract) + 0.1% butyric acid (HEOA). The impact of these supplements on body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), haemato-biochemical parameters, carcass characteristics, and economics were assessed in 42 days of experiment. The results revealed that BWG of birds were significantly (p <0.05) higher in HEOA, HE and PC group compared with NC. FI and FCR of HE, OA, and HEOA groups were significantly (p <0.05) lower than NC and PC group showed the lowest FCR. Phytobiotic mixture and OA both alone and in combination showed significantly (p <0.05) higher serum glucose and globulin level than NC with no difference to PC group. HE and HEOA groups had a significantly (p <0.05) higher A:G ratio than other groups. The serum cholesterol was lower (p <0.05) in HE, OA, and HEOA groups than PC group birds. No significant effect of phytobiotic and organic acid was observed on the drawn yield of broilers. It was concluded that supplementation of alcoholic extract of 1% phytobiotic mixture with 0.1% butyric acid improved the performance of birds without any detrimental effect on their health.